Ionic Liquid-Containing Polymers

By incorporating an adhesive and a hydrophobic ionic liquid into the ionic liquid-containing polymer, the challenges of attaching comparison electrodes are addressed, resulting in improved adhesion, reduced manufacturing costs, and increased design flexibility.

JP7664903B2Active Publication Date: 2025-04-18HORIBA ADVANCED TECHNO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022505183
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-03
Filing Date
2021-02-26
Publication Date
2025-04-18
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

Conventional ionic liquid-containing polymers used as salt bridges for comparison electrodes require separate adhesives or fixtures for attachment, increasing manufacturing costs and limiting design flexibility, especially for smaller or specially shaped electrodes.

Method used

An ionic liquid-containing polymer is developed that incorporates an adhesive and a hydrophobic ionic liquid, allowing the polymer itself to possess adhesiveness. This eliminates the need for separate adhesives or fixing devices, enabling direct attachment to electrodes and reducing manufacturing costs.

Benefits of technology

The integrated adhesive properties of the ionic liquid-containing polymer improve adhesion between the electrode and the polymer, stabilize the comparison electrode's potential, and allow for a more flexible and miniaturized design, while reducing production efforts and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664903000003
    Figure 0007664903000003
  • Figure 0007664903000004
    Figure 0007664903000004
  • Figure 0007664903000005
    Figure 0007664903000005
Patent Text Reader

Abstract

Provided is an ionic-liquid-containing polymer that enables reference electrodes and the like to be made even smaller and allows for further improvement in freedom of design while suppressing manufacturing costs. The ionic-liquid-containing polymer is used as a salt bridge for a reference electrode, and is characterized by containing an adhesive and a hydrophobic ionic liquid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ionic liquid-containing polymers for use, for example, as salt bridges in reference electrodes. [Background technology]

[0002] Conventionally, as described in Patent Document 1, an ionic liquid-containing polymer has been known which is used as a salt bridge for a reference electrode in which a hydrophobic ionic liquid (hereinafter, also referred to as IL) has been gelled, and which utilizes the properties of the hydrophobic ionic liquid to almost completely prevent evaporation or leakage of the electrolyte.

[0003] However, when a conventional ionic liquid-containing polymer is attached to, for example, a silver / silver chloride electrode of a comparison electrode, it is necessary to use a separately prepared adhesive, fastener, or the like, which poses the problem that the production cost of the comparison electrode increases when the comparison electrode is made smaller or has a special shape. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2008 / 032790 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above-mentioned problems, and has as its object to provide an ionic liquid-containing polymer which enables the comparison electrode and the like to be further miniaturized and allows for greater freedom in design while keeping production costs down. [Means for solving the problem]

[0006] That is, the ionic liquid-containing polymer according to the present invention is an ionic liquid-containing polymer used as a salt bridge for a reference electrode, and is characterized by containing an adhesive and a hydrophobic ionic liquid.

[0007] Such an ionic liquid-containing polymer can be endowed with adhesiveness itself while taking advantage of the hydrophobic properties of the ionic liquid. As a result, for example, even when the comparison electrode or the like is made smaller than conventional ones or has a special shape, the ionic liquid-containing polymer can be directly attached to the required portion without using a separately prepared adhesive, fixing device, or the like, so that the production of the comparison electrode or the like is not time-consuming and the production costs can be reduced.

[0008] Furthermore, since the ionic liquid-containing polymer itself has adhesive properties, it is possible to improve the adhesion between, for example, a silver / silver chloride electrode and the ionic liquid-containing polymer, and thereby to make the potential of a reference electrode, etc., more stable, compared to the conventional method of attachment using a separately prepared adhesive or fastener.

[0009] In a specific embodiment of the present invention, the adhesive is an epoxy-based or silicone-based synthetic resin adhesive. If the adhesive contains fluorine atoms, the compatibility between the adhesive and the hydrophobic ionic liquid can be further improved, particularly when the hydrophobic ionic liquid contains a polar group such as a fluorine atom.

[0010] The method for producing the ionic liquid-containing polymer is characterized by mixing an adhesive with a hydrophobic ionic liquid, followed by drying. The method for producing the ionic liquid-containing polymer involves very simple operations, and therefore the production costs of the ionic liquid-containing polymer itself can be kept low. Effect of the Invention

[0011] According to the present invention, it is possible to make use of the properties of hydrophobic ionic liquid, such as its resistance to evaporation and resistance to electrolyte leakage, while imparting adhesiveness to the ionic liquid-containing polymer itself. Therefore, when attaching the ionic liquid-containing polymer, there is no need to use a separately prepared adhesive or fastener, and the labor and number of parts required in manufacturing the reference electrode can be reduced. As a result, it is possible to achieve both further miniaturization of the reference electrode and improved freedom in terms of shape, as well as low cost.

[0012] In addition, since the ionic liquid-containing polymer itself has adhesive properties, the adhesion between the electrode and the ionic liquid-containing polymer can be improved compared to the conventional case in which a separately prepared adhesive is used, thereby making it possible to more stabilize the potential of the reference electrode, etc.

[0013] Furthermore, since the ionic liquid-containing polymer contains the adhesive, flexibility can be improved compared to conventional gels of ionic liquids. As a result, it is possible to make the reference electrode using the ionic liquid-containing polymer flexible so that it can flexibly respond to changes in shape, such as bending. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic diagram showing an ion concentration measuring device according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic diagram showing a sensor unit according to the embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic end view showing a comparison electrode according to an embodiment of the present invention. [Figure 4] FIG. 2 is a schematic diagram showing a usage form of the comparison electrode according to the present embodiment. [Diagram 5] FIG. 4 is a schematic end view showing a comparison electrode according to another embodiment of the present invention. [Figure 6] FIG. 2 is a diagram illustrating a schematic diagram of ion-electron conversion in each comparison electrode of the present invention. [Explanation of symbols]

[0015] 4. Ionic Liquid-Containing Polymer 22... Working electrode (ion-selective electrode) 23...Reference electrode DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The ionic liquid-containing polymer according to this embodiment is used in, for example, an electrochemical measurement device such as a multi-ion sensor type ion concentration measurement device capable of simultaneously measuring the concentrations, electrical conductivities, etc. of multiple types of ions.

[0017] As shown in FIG. 1, for example, this ion concentration measuring device 200 includes a sensor unit 100 that comes into contact with a sample solution and detects ions and the like contained in the sample solution, a calculation section 300 that calculates the ion concentration and the like based on an output value output from the sensor unit 100, a display section 400 that displays the measurement values ​​and the like calculated by the calculation section 300, and a control section 500 that controls the calculation section 300 and the display section 400. It is equipped with the following:

[0018] The sensor unit 100 includes, for example, as shown in Figures 2(a) and (b), a film-like substrate 1 having a length of about 3 cm, a width of about 1 cm and a thickness of about 0.5 mm and made of a liquid crystal polymer, polyvinyl chloride, polyethylene terephthalate or the like, and an electrode portion 2 and a thermistor 3 provided on the substrate 1. FIG. 2(a) is a schematic diagram showing an end face of the sensor unit 100, and FIG. 2(b) is a schematic diagram showing the surface of the sensor unit 100 opposite to the surface that comes into contact with a sample solution.

[0019] In this embodiment, the calculation section 300, the display section 400, and the control section 500 are performed by an information processing circuit 600 provided separately from the sensor unit 100. This information processing circuit 600 includes a digital circuit configured with a CPU, memory, communication port, etc., an analog circuit equipped with a buffer, amplifier, etc., and an AD converter, a DA converter, etc. that mediate between the digital circuit and the analog circuit. The CPU and its peripheral devices work together according to a predetermined program stored in the memory, and this information processing circuit 600 fulfills the functions of the calculation unit 300, the display unit 400, and the control unit 500.

[0020] The electrode portion 2 will be described in detail below. The electrode unit 2 includes, for example, an electrical conductivity meter 21, an ion-selective electrode 22 which is a working electrode, a comparison electrode 23, and the like, each of which is connected to the information processing circuit 600 by printed wiring formed on the base material 1.

[0021] The electrical conductivity meter 21 comprises a through hole 21H for an electrical conductivity meter formed in the base material 11, two electrodes 21E attached to the surface of the base material 1 opposite the surface that contacts the sample solution, so as to sandwich the through hole 21H for the electrical conductivity meter, and a housing 21C for receiving the sample solution formed to cover these two electrodes.

[0022] In this embodiment, the ion selective electrode 22 is, for example, a pH electrode 221 that measures the hydrogen ion concentration in the sample solution, a sodium ion selective electrode 222 that measures the sodium ion concentration, and a potassium ion selective electrode 223 that measures the potassium ion concentration. The pH electrode 221 comprises a pH electrode through hole 221H formed in the substrate 1, and an ISFET electrode 221E, and the ISFET electrode 221E is attached to the surface of the substrate 1 opposite to the surface that comes into contact with the sample solution, so that the ion-sensitive membrane 221S of the ISFET electrode 221E comes into contact with the sample solution via the pH electrode through hole 221H.

[0023] The sodium ion selective electrode 222 comprises a sodium ion selective electrode through-hole 222H formed in the base material 1, an ion-sensitive membrane 222M attached so as to cover the sodium ion selective electrode through-hole 222H, an internal electrode 222E made of, for example, a silver / silver chloride electrode attached to the surface of the base material 1 opposite to the surface that contacts the sample solution, and a gel-like internal liquid attached on the base material 1 so as to cover the internal electrode 222E and to be in contact with both the internal electrode 222E and the ion-sensitive membrane 222M. The potassium ion selective electrode 223 comprises a potassium ion selective electrode through-hole 223H formed in the base material 1, an ion-sensitive membrane 223M attached so as to cover the potassium ion selective electrode through-hole 223H, an internal electrode 223E made of, for example, a silver / silver chloride electrode attached to the surface of the base material 1 opposite to the surface that contacts the sample solution, and a gel-like internal liquid attached to the base material 1 so as to cover the internal electrode 223E and to be in contact with both the internal electrode 223E and the ion-sensitive membrane 223M.

[0024] The comparison electrode 23 functions as a reference electrode for the ion selective electrode 22, and comprises a comparison electrode through-hole 23H formed in the substrate 1, an internal electrode 23E made of, for example, a silver / silver chloride electrode and attached to the surface of the substrate 1 opposite to the surface of the substrate 1 that contacts the sample solution, and an ionic liquid-containing polymer 4 attached on the substrate 1 so as to cover the internal electrode 23E and the comparison electrode through-hole 23H.

[0025] The ionic liquid-containing polymer 4 contains an adhesive and a hydrophobic ionic liquid. The adhesive is preferably one or more selected from polyvinyl chloride (PVC), polystyrene, acrylate, polyvinyl butyral, polyamide, polyimide, polyurethane, polytetrafluoroethylene (PTFE), polysiloxane, copolymer of vinylidene fluoride and hexafluoropropylene (PVDF-HFP), and fluoropolysiloxane. These may be used alone or in combination. In this embodiment, fluoropolysiloxane is used as an example of the adhesive. In addition, in this embodiment, as an example of the hydrophobic ionic liquid, [C 8mim ][C1C1N] is used.

[0026] The ionic liquid-containing polymer 4 can be produced by mixing a predetermined amount of the adhesive and the hydrophobic ionic liquid. In this embodiment, for example, the hydrophobic ionic liquid [C 8mim The adhesive is prepared by adding the fluoropolysiloxane to a mixture of 1:1 hydrophobic ionic liquid and adhesive together with a suitable solvent such as tetrahydrofuran to the hydrophobic ionic liquid [C1C1N] and mixing thoroughly. The ionic liquid-containing polymer 4 thus produced is applied to an internal electrode, such as a silver / silver chloride electrode, and dried for use as a salt bridge for the comparison electrode 23.

[0027] The ionic liquid-containing polymer 4 thus configured and the ion concentration measuring device 200 using the same can provide the following effects. The ion-containing polymer contains, as a hydrophobic ionic liquid, [C 8mim [C1C1N], when used as a salt bridge for the comparison electrode 23 as described in the above embodiment, the dissolution rate of the ionic liquid-containing polymer 4 into a sample solution can be kept extremely slow, thereby preventing contamination of the sample solution.

[0028] In addition, since the ionic liquid has extremely low volatility, there is no need to take into consideration the volatilization of the ionic liquid-containing polymer 4 in the design, and the configuration of the comparison electrode 23 can be simplified and further miniaturized.

[0029] Furthermore, since the ionic liquid-containing polymer 4 contains fluoropolysiloxane as the adhesive, the ionic liquid-containing polymer 4 itself can have sufficient adhesiveness. As a result, when attaching the ionic liquid-containing polymer 4 to the comparison electrode 23, there is no need to use a separately prepared adhesive, fastener, etc., and the effort and number of parts required to manufacture the comparison electrode 23 can be reduced. In this way, it is possible to achieve further miniaturization of the reference electrode 23, improved freedom in its shape, and low cost at the same time.

[0030] Since the ionic liquid-containing polymer 4 itself has adhesive properties, the adhesion between the electrode and the ionic liquid-containing polymer 4 is improved compared to the conventional case in which a separately prepared adhesive is used, and the potential of the comparison electrode 23 etc. can be more stabilized.

[0031] Although this is merely a supposition, it is thought that since both the adhesive and the hydrophobic ionic liquid contain fluorine atoms, the adhesive and the hydrophobic ionic liquid are compatible with each other and are difficult to separate.

[0032] As described above, the ionic liquid-containing polymer 4 has extremely low volatility and does not need to be contained in a case that protects the internal liquid from evaporation, so that the sodium ion selective electrode 222 and the potassium ion selective electrode 223 can be made even smaller than before. The ionic liquid-containing polymer 4 contains the adhesive, and therefore can have improved flexibility as compared with conventional gels of ionic liquid. As a result, the ion concentration measuring device 200 including the reference electrode 23 can be made flexible and can flexibly respond to shape changes such as bending and twisting. Since the reference electrode 23 can be made flexible as described above, it is possible to make the sensor unit 100 into a wearable multi-sensor unit that can be worn directly on human skin, for example. Such a sensor unit 100 can also be used for measuring trace amounts of samples such as biological samples and soil components. Furthermore, since the production is simple, the production cost of the reference electrode can be reduced and the reference electrode can be made into a disposable electrode.

[0033] The present invention is not limited to the above-described embodiment. For example, the adhesive is not particularly limited as long as it has a certain degree of adhesive strength, and may be any adhesive that can be mixed with the hydrophobic ionic liquid without undergoing phase separation. The adhesive may be, for example, a natural rubber adhesive or a synthetic resin adhesive. Examples of the synthetic resin adhesive include acrylic adhesives, olefin adhesives, urethane adhesives, silicone adhesives, vinyl chloride adhesives, epoxy adhesives, polyamide adhesives, and polyimide adhesives. The adhesive may be one selected from these, or two or more of these adhesives may be used in combination. In particular, epoxy-based and silicone-based materials are easy to mix with the hydrophobic ionic liquid and are easy to use.

[0034] The hydrophobic ionic liquid can be one formed from a cation and anion having approximately the same standard Gibbs energy of transfer between the ionic liquid and water. The standard Gibbs energy of transfer between an ionic liquid and water means the Gibbs (free) energy required for a cation or anion constituting an ionic product to transfer between an ionic liquid and water under standard conditions (0.1 MPa, 25°C). The energies being approximately the same in magnitude may be approximately the same in terms of order of magnitude. A hydrophobic ionic liquid refers to an ionic liquid in which the sum of the ionic liquid-water Gibbs energies of the cations and anions that compose it is approximately 30 kJ / mol or less under the standard conditions. An ionic liquid that satisfies this condition is a type of sparingly soluble salt that is sparingly soluble in water.

[0035] Specific examples of cations and anions having approximately the same standard Gibbs energy of transfer between an ionic liquid and water include the following. The cation may be, for example, at least one of a quaternary ammonium cation, a quaternary phosphonium cation, or a quaternary arzonium cation, more specifically, (C2H5)4N+, C 4mim + , C 6mim + , C 8mim + Or C 10mim + C etc. imim (1-alkyl-3-methylimidazolium ion (i represents the number of carbon atoms in the alkyl group)), (n-C3H7)4N + , (n-C4H9)4N + , Ph4As + At least one of the above may be mentioned.

[0036] The anion may be, for example, [R 1 SO2NSO2R 2 ]-(R 1 and R 2 are perfluoroalkyl groups having 1 to 12 carbon atoms), C2F5BF3 - , C3F7BF3 - or C4F9BF3 - Fluorine-containing borate ions such as B(CN)4 -, (Tetracyanoborate), BEHSS - (Bis(2-ethylhexyl)sulfosuccinate), C1C1N - (bis(trifluoromethylsulfonyl)imide ion), P(C n F 2n+1 )3F3 - (Here, n is 1 to 6. The same applies below.) (CF3SO2)3C - , AsF6 - , SbF6 - , (C n F 2n+1 )SO3 - , or (C n F 2n+1 )COO - At least one of the above can be mentioned. Such hydrophobic ionic liquids consisting of cations and anions can be appropriately selected and used depending on the application.

[0037] The ionic liquid-containing polymer 4 may be a mixture of the adhesive and the hydrophobic ionic liquid in a weight ratio of about 100:10 to 10:300, more preferably about 100:50 to 100:200, and an appropriate solvent may be used to mix them well. If necessary, a plasticizer such as dioctyl phthalate (n-DOP) may be added to the ionic liquid-containing polymer 4.

[0038] The comparison electrode 23 may further include an ion-electron conversion layer 6 between the ionic liquid-containing polymer 4 used as the salt bridge and the internal electrode 23E, 222E or 223E, which mediates electrical connection between the ionic liquid-containing polymer 4 and the internal electrode 23E, 222E or 223E by electronic conduction. As an example, a comparison electrode including an ion-electron conversion layer 6 is shown in FIG.

[0039] 5, it is preferable that the ion-electron conversion layer 6 covers the entire surface of the internal electrode 23E facing the sample solution, and that the entire surface of the ion-electron conversion layer 6 facing the sample solution is covered with the ionic liquid-containing polymer 4. In this way, it is possible to prevent moisture and the like from entering between the ionic liquid-containing polymer 4 and the ion-electron conversion layer 6, or between the ion-electron conversion layer 6 and the internal electrode 23E. The ion-electron conversion layer 6 contains one or more components capable of converting ions and electrons, such as carbon nanotubes, graphene, or graphite.

[0040] By providing an ion-electron conversion layer 6 between the ionic liquid-containing polymer 4 and the internal electrode 23E in this manner, it is possible to improve electrical adhesion compared to the case where the ionic liquid-containing polymer 4 is in direct contact with the internal electrode 23E, as shown in Figure 6.

[0041] In the above embodiment, as shown in FIG. 6(a), the internal electrodes are made of silver / silver chloride. However, as shown in FIG. 6(b), if the internal electrodes are made of a metal such as gold or platinum, the ion-electron conversion between the ion-electron conversion layer 6 and the internal electrodes can be omitted, thereby further improving the response speed.

[0042] The sodium ion selective electrode 222 or the potassium ion selective electrode 223 may further include an internal liquid such as a 3.3 mol / L KCl aqueous solution, and a case that contains the internal liquid.

[0043] The ion selective electrode 22 may be not only the pH electrode 221, the sodium ion selective electrode 222, or the potassium ion selective electrode 223 described above, but also one that detects the concentration of other types of ions, and a plurality of electrodes that detect the concentrations of the same type of ion or different types of ions may be used in any combination. In addition, various modifications and combinations of the embodiments may be made as long as they do not go against the spirit of the present invention. EXAMPLES

[0044] The ionic liquid-containing polymer 4 according to the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. <Example 1> In this example, various ionic liquid-containing polymers 4 were prepared by varying the types and blending ratios of the hydrophobic ionic liquid and the adhesive, and their properties were compared with those of a conventional gel of an ionic liquid. Four samples of the same composition were prepared using the same procedure for each of these samples.

[0045] The composition of the ionic liquid-containing polymer 4 prepared in this example is shown in Table 1 below. In Table 1, Ionic liquid 1 is [C 8mim [C1C1N]475.47g / mol, Matrix R is polyvinyl chloride (average degree of polymerization 2500), Matrix A is RTV silicone rubber SE9176 (Shin-Etsu Chemical Co., Ltd.), Matrix B is RTV silicone rubber FE2000 (Shin-Etsu Chemical Co., Ltd.), Matrix C is EP-001K (Cemedine Co., Ltd.), and Matrix D is EP-008 (Cemedine Co., Ltd.). Of these samples, R-1, R-2, and R-3 represent gels of conventional ionic liquids, while A-1, B-1, B-2, C-1, D-1, D-2, and D-3 represent ionic liquid-containing polymer 4 according to the present invention.

[0046] [Table 1]

[0047] Each of the samples prepared in Table 1 was applied onto the silver / silver chloride electrode E of a card sensor 5 having a silver / silver chloride electrode E printed on a substrate P made of a liquid crystal polymer, as shown in FIG. 3, and then cured. The method for producing this card sensor 5 is as follows. First, a silver / silver chloride paste was applied to the substrate P made of the liquid crystal polymer, and then dried overnight. Next, a polyvinyl chloride plate V having a hole H with a diameter of 2 mm was attached to the substrate P with double-sided tape so that the hole H was positioned above the silver / silver chloride electrode E. 25 μl of each sample in Table 1 was dropped into the hole H of the polyvinyl chloride plate V, and then dried overnight.

[0048] The card sensor 5 thus prepared was immersed together with a silver wire in a 0.2 M KCl aqueous solution, and the film resistance was measured using an electric conductivity meter (DS-74, manufactured by Horiba, Ltd.). The cure state and resistance value of each sample are summarized in Table 2 below.

[0049] [Table 2]

[0050] The results in Table 2 show that the ionic liquid-containing polymer, which contains an adhesive and a hydrophobic ionic liquid, is more flexible than conventional ionic liquid gels, and therefore it is believed that ionic liquid-containing polymer 4 will be less likely to break even if it is used to make a flexible sheet-like electrode. It was also found that ionic liquid-containing polymer 4, which contains an adhesive and a hydrophobic ionic liquid, had a lower and more stable resistance value than conventional ionic liquid gels. It was found that the resistance value tended to decrease as the content of hydrophobic ionic liquid increased. One of the reasons why the resistance value is low and stable is believed to be that the adhesive and the hydrophobic ionic liquid are mixed uniformly without being separated. In addition, since the ionic liquid-containing polymer 4 of the present invention has adhesive properties, it is believed that the higher adhesion to the silver / silver chloride electrode E compared to conventional ionic liquid gels is also a factor in the lower resistance value.

[0051] Furthermore, the card sensor 5 that had been coated with sample B-2 or C-1 and cured was used together with a double junction type reference electrode R (2565A-10T, Horiba, Ltd.) as shown in FIG. 4, and immersed in buffer solutions of pH 7, pH 4, and pH 9, in that order, for 3 minutes each, to record the change in potential over time, and the liquid junction potential was calculated from the potential 3 minutes after immersion in each solution. As a result, the card sensor 5 using C-1 had a liquid junction potential within ±5 mV when immersed in buffer solutions of pH 7, pH 4, and pH 9 and a 0.2 mol / L KCl aqueous solution. The card sensor using B-2 also showed a liquid junction potential difference similar to that of the card sensor using C-1 described above. From these results, it was found that the card sensor 5 using the ionic liquid-containing polymer 4 as a salt bridge can be satisfactorily used as a reference electrode. [Industrial Applicability]

[0052] It is possible to provide an ionic liquid-containing polymer that enables the reference electrode and the like to be further miniaturized and allows for greater freedom in design while keeping production costs down.

Claims

1. 1. An ionic liquid-containing polymer for use as a salt bridge in a reference electrode, comprising: The adhesive contains a fluorine atom and a hydrophobic ionic liquid, The ionic liquid-containing polymer itself has adhesive properties, An ionic liquid-containing polymer that can be directly attached to the inner electrode of a reference electrode.

2. 2. The ionic liquid-containing polymer according to claim 1, wherein the adhesive is an epoxy-based or silicone-based synthetic resin adhesive.

3. Mixing an adhesive containing fluorine atoms with a hydrophobic ionic liquid and drying the mixture; The method for producing an ionic liquid-containing polymer is such that the ionic liquid-containing polymer itself has adhesive properties and can be directly attached to the internal electrode of a reference electrode.

4. 10. A reference electrode comprising the ionic liquid-containing polymer according to claim 1 as a salt bridge.

5. Equipped with an internal electrode, 5. The reference electrode according to claim 4, further comprising an ion-electron conversion layer between said salt bridge and said internal electrode.

6. 6. The comparative electrode according to claim 5, wherein the ion-electron conversion layer contains at least one material selected from the group consisting of carbon nanotubes, graphene, and graphite.

7. 7. An electrochemical measuring device comprising the reference electrode according to claim 4.

Citation Information

Patent Citations

  • A device for providing means for internal calibration in an electrochemical sensor

    JP2012520462A

  • Reference electrode and spontaneous potential measuring method

    JP2014062782A

  • Corrosion sensor for concrete structures and method of detecting corrosion

    JP2018009819A

  • Reference electrode and method for manufacturing a reference electrode

    US20190195824A1

  • Reference electrode coated with ionic liquid, and electrochemical measurement system using the reference electrode

    WO2008032790A1